The World War I diary of George Martin Farrow, C. B. E Gallipoli, the Somme and beyond - Farrow, George Martin 1896-1969 (Hill, 2009)
The life of George Martin Farrow, a WW1 double amputee & his post war work for the disabled.
The life of George Martin Farrow, a WW1 double amputee & his post war work for the disabled.
Keywords: Weltkrieg (1914-1918); Soldiers -- Australia -- Diaries; World War, 1914-1918 -- Personal narratives, Australian; World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula; Amputees -- Australia -- Biography; Disabled veterans -- Australia -- Biography; People with disabilities -- Australia -- Care; Erster Weltkrieg; Soldat; Australien; Türkei; Biografie; Erlebnisbericht; Tagebuch